EXTH-12. EFFECT OF THE PROTEIN ARGININE METHYLTRANSFERASE PRMT5 INHIBITION IN GLIOMA STEM-LIKE CELLS. (5th November 2018) - Mittal, Sandeep; Shaw, Vikram; Piao, Yuji; Young Park, Soon; Sriram, Sai; Dong, Jianwen; Martinez-Ledesma, Emmanuel; Henry, Verlene; Ezhilarasan, Ravesanker; Sulman, Erik; Balasubramaniyan, Veerakumar; de Groot, John
Abstract: Protein arginine methyltransferases (PRMTs) have gained significant scientific attention due to their ability to regulate various biological functions including epigenetic regulation, cell differentiation, signal transduction and most importantly their dysregulation in human disease including cancer. Among various cancers, Glioblastoma is the most aggressive primary malignant brain tumor with few effective therapies. Currently, in glioblastoma therapy, the high expression level of Protein arginine methyltransferase 5 (PRMT5) has been reported as a therapeutic target which represses the transcription of a target gene via forming symmetric dimethylarginine (SDMA) residues. By using a panel of molecularly distinct glioma stem like cells (GSCs) we investigated the effect of PRMT5 inhibitor GSK591 on cell viability. Furthermore, genomic, proteomic (reverse protein lysate array, RPPA), methylation status and GSC subtype were correlated with GSK591 IC50 to find predictors of drug sensitivity. Western blotting data showed high expression of PRMT5 and multiple bands of SDMAs in most GSCs tested (n=31) irrespective of molecular subtype, indicating PRMT5 enzymatic activity in GSC cell lines. However, there is only a small subset of 4 GSC lines (13%) as showed complete inhibition of SDMA expression at low doses (< 1.5 µM) in dose- and time-dependent fashion after GSK591 treatment. The sensitivity of GSK591 correlated with low methylation of multiple genes pre-treatment, including MAGI2, EGR2, and DUSP16. In addition, up-regulated genes in sensitive GSCs correlated with proliferation signatures using gene set enrichment analyses (GSEA). Including this, we also found the upregulation of senescence marker along with activation of autophagy genes (Beclin-1 and Akt) in GSCs sensitive to GSK591. Tight regulation of Akt-mTOR pathway enables cancer cells to survive in harsh conditions via activation of autophagy signaling. Currently, we are investigating the role of PRMT5 in tumor growth through the concomitant regulation of autophagy signaling in GSCs.